Pengaruh Fundamental Dan Teknikal Analisis Terhadap Pemilihan Emiten Investasi Saham Pada PT. Harum Energy Tbk (HRUM) - Gian Alfreda Wirawan; Yanda Bara Kusuma (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
The growth of the capital market in Indonesia is currently of great interest to the public. Being an investor in the capital market provides benefits, but each investment instrument certainly has its own risks. This research aims to provide information to potential investors at PT Harum Energy (HRUM) using fundamental analysis and technical analysis with data obtained through online websites that provide information regarding company financial reports and candle chart patterns or price history of a company. Provide views to determine which issuer to choose. Fundamental analysis by looking at the value of Earning per Share (EPS), Price Earning Ration (PER), Debt Equity Ration (DER). Then technical analysis using the theory of Patern Chart Patterns, golden crosses, Relative Strength Index (RSI). The results of this research provide results that can later be considered when choosing PT Harum Energy shares as an investment option.